2002
DOI: 10.1002/pros.10162
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia increases the aggressive characteristics and survival properties of prostate cancer cells

Abstract: This study demonstrates that even acute hypoxia has the potential to drastically alter the growth, differentiation characteristics, and apoptotic sensitivity of a prostate cancer cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 27 publications
(28 reference statements)
4
69
0
Order By: Relevance
“…23,24 Studies have shown that there are significant associations between intratumoral hypoxia and tumor metastases, response to chemotherapy or radiotherapy and prognosis of cancer patients. [33][34][35][36][37] It has been shown that hypoxia modulates the expression of different sets of genes in cancer cells. 36 To generate gene therapy vectors that are effective for hypoxic tumor cells, it is crucial to use transcriptional control elements that are active in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Studies have shown that there are significant associations between intratumoral hypoxia and tumor metastases, response to chemotherapy or radiotherapy and prognosis of cancer patients. [33][34][35][36][37] It has been shown that hypoxia modulates the expression of different sets of genes in cancer cells. 36 To generate gene therapy vectors that are effective for hypoxic tumor cells, it is crucial to use transcriptional control elements that are active in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] It has been shown that hypoxia modulates the expression of different sets of genes in cancer cells. 36 To generate gene therapy vectors that are effective for hypoxic tumor cells, it is crucial to use transcriptional control elements that are active in these cells. The effect of hypoxia on the expression of the survivin gene was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One specific HIF-2α target gene is Oct-4, which encodes a transcription factor essential for the pluripotency of stem cells. Its activation is responsible for tumor cell dedifferentiation that has been demonstrated in neuroblastomas, breast cancer, and is probably the same in other tumours [49][50][51] . Activation of the Notch signaling pathway also participates in the loss of cell differentiation 52,53 .…”
Section: Biological Functionsmentioning
confidence: 99%
“…Colorectal cancer stem cells cultured at hypoxia show increased clonogenicity, inhibited differentiation and induced expression of markers associated with a stem cell-like phenotype (75). Also, prostate carcinoma LNCaP cells exposed to hypoxia downregulate differentiation-specific proteins such as prostatespecific antigen and androgen receptor, suggesting that dedifferentiation in response to hypoxia occurs also in prostate cancer (76).…”
Section: Hypoxia and Tumor Cell Differentiationmentioning
confidence: 99%